Investigations of the origins of altered pain perception in a commercial pig strain - Owles, Catherine (2019)
Lameness affects over 20% of commercial pigs in the UK and is a significant threat to the sustainability of current pig production techniques worldwide, raising animal welfare, economic and food security concerns. Among the most common causes of porcine lameness are joint diseases such as osteochondrosis (OC), a skeletal disease affecting bone growth, and osteoarthritis (OA), which results from the progressive breakdown of articular cartilage. OC and OA are reported to affect over 80% of commercial pigs, however, despite this prevalence, the diseases are poorly characterised in pigs. OA also affects over 8.75 million people in the UK, so spontaneous porcine OA could provide a useful animal model of the human condition. The aims of this thesis were to characterise the pathological features of spontaneous OC and OA in a commercial pig strain, examining their relationship to pain and inflammation and identifying the molecular mechanisms involved. Spontaneous porcine OA could then be evaluated as a model for the human disease.